2015
DOI: 10.1007/s10096-015-2441-7
|View full text |Cite
|
Sign up to set email alerts
|

Target site antimicrobial activity of colistin might be misestimated if tested in conventional growth media

Abstract: Cation-dependent inhibition of antimicrobial activity was reported for polymyxin antibiotics. Ca(2+) and Mg(2+) concentrations recommended by the Clinical and Laboratory Standards Institute (CLSI) for the supplementation of Müller-Hinton broth (MHB) are markedly lower than interstitial space fluid (ISF) concentrations in vivo. Hence, it was speculated that the antimicrobial activity of colistin might be overestimated if tested using conventional cation-adjusted MHB. The antimicrobial activity of colistin again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
0
12
0
5
Order By: Relevance
“…They might miss the HR phenotype because of the low bacterial load used in these methods, a load that is inappropriate to detect the (low-frequency) resistant subpopulation. In addition, colistin activity might be overestimated if tested in cation-adjusted Mueller-Hinton (MH) broths (as recommended) compared to interstitial space fluid-like media possibly causing a shift from susceptible to resistant in A. baumannii (37). On the other hand, adsorption of polymyxins to plastics might overestimate colistin MICs, which can be prevented by the use of low-protein-binding polypropylene (38).…”
Section: Discussionmentioning
confidence: 99%
“…They might miss the HR phenotype because of the low bacterial load used in these methods, a load that is inappropriate to detect the (low-frequency) resistant subpopulation. In addition, colistin activity might be overestimated if tested in cation-adjusted Mueller-Hinton (MH) broths (as recommended) compared to interstitial space fluid-like media possibly causing a shift from susceptible to resistant in A. baumannii (37). On the other hand, adsorption of polymyxins to plastics might overestimate colistin MICs, which can be prevented by the use of low-protein-binding polypropylene (38).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the calcium concentration recommended by the CLSI for determining colistin susceptibility in vitro is 2-fold higher than the concentration found in human interstitial space fluid in vivo (92). A recent study revealed that the MIC of colistin might be misestimated if tested with conventional cation-adjusted growth media (overestimation for P. aeruginosa and A. baumannii and underestimation for E. coli) (92). The use of cation-adjusted or non-cation-adjusted medium therefore remains questionable, and a consensus is still needed.…”
Section: Impact Of Materials On Mic Determinationmentioning
confidence: 91%
“…In fact, it is suspected that the colistin antimicrobial activity might be overestimated if tested using conventional cation-adjusted MH as recommended by the CLSI. Note that the calcium concentration recommended by the CLSI for determining colistin susceptibility in vitro is 2-fold higher than the concentration found in human interstitial space fluid in vivo (92). A recent study revealed that the MIC of colistin might be misestimated if tested with conventional cation-adjusted growth media (overestimation for P. aeruginosa and A. baumannii and underestimation for E. coli) (92).…”
Section: Impact Of Materials On Mic Determinationmentioning
confidence: 99%
“…They might miss the heteroresistant phenotype because of the low bacterial load used in these methods, a load that is inappropriate to detect the (low) frequency resistant subpopulation. In addition, colistin activity might be overestimated if tested in cation-adjusted Mueller-Hinton broths (as recommended) as compared to interstitial space fluid-like media possibly causing a shift from susceptible to resistant in A. baumannii (37). At the opposite, adsorption of polymyxins to plastics might overestimate colistin MICs which can be prevent by the use of low-protein-binding polypropylene (38).…”
Section: Discussionmentioning
confidence: 99%